2018
DOI: 10.1111/ecog.03984
|View full text |Cite
|
Sign up to set email alerts
|

The fluctuating world of a tundra predator guild: bottom‐up constraints overrule top‐down species interactions in winter

Abstract: Global warming is predicted to change ecosystem functioning and structure in Arctic ecosystems by strengthening top-down species interactions, i.e. predation pressure on small herbivores and interference between predators. Yet, previous research is biased towards the summer season. Due to greater abiotic constraints, Arctic ecosystem characteristics might be more pronounced in winter. Here we test the hypothesis that top-down species interactions prevail over bottom-up effects in Scandinavian mountain tundra (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 47 publications
4
48
0
Order By: Relevance
“…Moreover, adding midge carcasses to heathlands near Mývatn increased grass cover, plant biomass, detritivore and herbivore densities, and abundances of several predator groups (e.g., predaceous beetles and parasitoids) (Hoekman et al 2011, Gratton et al 2017). These results are also consistent with how pulsed resources influence food webs in other nutrient‐poor ecosystems, which are generally controlled by bottom‐up forces (Sanchez‐Pinero and Polis 2000, Schwinning and Sala 2004, Stoessel et al 2019).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, adding midge carcasses to heathlands near Mývatn increased grass cover, plant biomass, detritivore and herbivore densities, and abundances of several predator groups (e.g., predaceous beetles and parasitoids) (Hoekman et al 2011, Gratton et al 2017). These results are also consistent with how pulsed resources influence food webs in other nutrient‐poor ecosystems, which are generally controlled by bottom‐up forces (Sanchez‐Pinero and Polis 2000, Schwinning and Sala 2004, Stoessel et al 2019).…”
Section: Discussionsupporting
confidence: 82%
“…) and in modelling species interactions within the terrestrial arctic predator guild (Stoessel et al. ) in mountain tundra ecosystems. But also in biotope mapping in urban and rural landscapes, rel‐NDVI ortho has shown to be useful to automatically separate vegetation covered land from non‐vegetation, which is a highly desirable separation, even without the attempt to translate rel‐NDVI ortho values into an estimation of primary productivity (Akbari et al.…”
Section: Discussionmentioning
confidence: 99%
“…We have applied rel-NDVI ortho in a number of recent studies where it has been shown to be useful in modelling lemming abundance on a 5-30 m scale (Le Vaillant et al 2018) and in modelling species interactions within the terrestrial arctic predator guild (Stoessel et al 2018) in mountain tundra ecosystems. But also in biotope mapping in urban and rural landscapes, rel-NDVI ortho has shown to be useful to automatically separate vegetation covered land from non-vegetation, which is a highly desirable separation, even without the attempt to translate rel-NDVI ortho values into an estimation of primary productivity (Akbari et al 2003;Grafius et al 2016;Sk anes and Stoessel 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Population dynamics models have been used to understand the effect of interspecific interactions and environment on species demography. However, these models are in general not demographically structured (Stenseth et al 2015, Pacoureau et al 2019a, Stoessel et al 2019) or only partially (Millon et al 2014, Saunders et al 2018, Pacoureau et al 2019b). Unstructured approaches consider individuals as being equivalent but differences in size, age and ontogenic stages exist within a population and may be of importance in the context of interspecific interactions.…”
Section: Introductionmentioning
confidence: 99%